Synthesis of stable and highly oxygen deficient V2O5 thin films for physical functionalization of nanofiltration membranes. (September 2019) - Indhumathi, S.R.; Manoj Cristopher, M.; Karthick, P.; Dhivya Pushpa, M.; Poornima, B.; Gopalakrishnan, C.; Jeyadheepan, K.
Abstract: Functionalization of nanofiltration membranes by physical modification of the membrane surface is the challenging field of research to enhance the stability of the membrane by reducing the membrane fouling. Herein, stable vanadium pentoxide (V2 O5 ) thin films, deposited by using the nebulizer spray pyrolysis technique by varying the precursor concentration, were reported for the application of the surface modification of nanofiltration membranes. The films were characterized to study their physical properties and hence to predict the optimized deposition conditions. The orthorhombic crystal phase and 2D nanorod-like morphology were observed for the optimized films which were inferred from the structural and surface morphological studies. Optical transparency of 78% and the optical band gap of 2.4 eV were determined from the optical studies. The highly oxygen deficient V2 O5 thin films deposited with the perfected precursor concentration of 0.15 M show the super-hydrophilic nature of the film (contact angle, θ < 20°) which is suitable for the functionalization of nanofiltration membranes.